Evaluation Of Impact Of Privatization On Financial Performance In Accepted Companies In Tehran Stock Exchange - Mohebbifard, Saeid (2009)
In this investigation effects of privatization policy in socio-economic rule and from financial view are examined. This policy is assessed based on accounting and privatization text with three ratios: earning per share return on assets and return on equity (profitability ratios).